Makna Relegius Tradisi Lawa Pipi (Lari Kambing) Lebaran Idul Adha pada Masyarakat Negeri Hila Maluku Tengah - Muhammad Idul Launuur (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to explain the meaning and symbols of goats in the Lawa Pipi (goat running) tradition in the Hili Country Community, Leihitu District, Central Maluku. This research uses an approach based on a descriptive approach which focuses on real problems that existed at the time the research was conducted. Through descriptive research, the author tries to describe the events of the Lawa Pipi (Goat Running) Eid al-Adha tradition in the people of Hila State, Central Maluku which is the center of attention without giving special treatment. Based on research carried out by data obtained by informants, the Lawa Pipi paga tradition of Eid al-Adha in Negeri Hila, Leihitu District, Central Maluku is a tradition that has been passed down by ancestors. The religiosity belief of the Lawa Pipi (Goat Running) Tradition is carrying a goat by circling the Hasan Soleman Mosque seven times, the people of Hila State interpret it as carrying out the Hajj pilgrimage around the Black Stone seven times, This is because the Lawa Pipi (Goat Running) tradition involves the Tawaf process where people experience the Tawaf journey directly even though they do not go to the city of Mecca. According to the community, the Lawa Pipi (Goat Running) tradition is carried out as an effort to get closer to Allah SWT and is believed to bring good fortune, long life and the desire to go to the Holy Land can be achieved.